Association of inflammatory disease and long-term outcomes among young adults with myocardial infarction: the Partners YOUNG-MI registry. (25th November 2020) - Weber, B; Biery, D.W; Singh, A; Divakaran, S; Berman, A.N; Wu, W; Brown, J.M; Liao, K; Bhatt, D.L; Di Carli, M; Blankstein, R
Abstract: Background: Autoimmune systemic inflammatory diseases are associated with an increased risk of cardiovascular disease, particularly myocardial infarction (MI). However, there are limited data on the prevalence and effects of inflammatory disease among U.S. adults who experience an MI at a young age. Purpose: We sought to determine the prevalence and prognostic value of inflammatory disease in U.S. adults who experience an MI at a young age. Methods: The YOUNG-MI registry is a retrospective cohort study of consecutive patients who experienced a Type 1 MI at or below the age of 50 years from 2000 to 2016 at two large medical centers. A diagnosis of rheumatoid arthritis (RA), psoriasis (PsO), systemic lupus erythematosus (SLE), or inflammatory arthritis was determined through physician review of electronic medical records (EMR). Demographic information, presence of cardiovascular (CV) risk-factors, medical procedures, and medications upon discharge were also ascertained from the EMR. Incidence of death was determined using a combination of EMR and national databases. Cox proportional hazard modeling was performed on a sub-sample following Mahalanobis Distance matching on age, sex, and CV risk factors. Results: The cohort consisted of 2097 individuals (median age 45 years, 19% female, 53% ST-elevation MI). Among these, 53 (2.5%) individuals possessed a diagnosis of systemic inflammatory disease at or before their index MI (23% SLE, 9% RA, 64% PsO, 4% inflammatory arthritis). When compared to the remainder of the cohort, patients with a diagnosis of systemic inflammatory disease were more likely to be female (36% vs 19%, p=0.004) and be diagnosed with hypertension (62% vs 46%, p=0.025). There was, however, no significant difference in the prevalence of other CV risk factors – diabetes, smoking, dyslipidemia – or a family history of premature coronary artery disease. Despite these similarities, patients with inflammatory disease were less likely to be prescribed aspirin (88% vs 95%, p=0.049) or a statin (76% vs 89%, p=0.008) upon discharge. Over a median follow-up of 11.2 years, patients with inflammatory disease experienced an increased risk of all-cause mortality when compared with the full-cohort (Figure). Compared to the matched sample (n=138), patients with systemic inflammatory disease exhibited an increased risk of all-cause mortality (HR=2.68, CI [1.18 to 6.07], p=0.018), which remained significant after multivariable adjustment for length of stay and GFR (HR=2.38, CI [1.02 to 5.54], p=0.045). Conclusions: Among individuals who experienced an MI at a young age, approximately 2.5% had evidence of a systemic inflammatory disease at or before their MI. When compared with a population of individuals with similar cardiovascular risk profiles, those with inflammatory disease had higher rates of all-cause mortality. Our findings suggest that the presence of a systemic inflammatory disorder is independently associated with worse long-term outcomes. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): 1. 5T32 HL094301 NIH T32 Training Grant, "Noninvasive Cardiovascular Imaging Research Training Program"